2021
DOI: 10.21873/invivo.12720
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Total Hip Arthroplasty: A Comparison of Restoring Hip Biomechanics With and Without a Traction Table

Abstract: Background/Aim: The aim of the study was to analyze operative time and restoration of hip biomechanics in total hip arthroplasty (THA) via direct anterior approach (DAA) with and without the use of a traction table. Patients and Methods: We retrospectively compared 97 cases where a traction table was used to 92 cases without a table. Ninetyseven patients received THA with a traction table (AMIS ® technique) and 92 patients with conventional DAA. Postoperative standard radiographs were used to analyze offset pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Due to the traction table, the authors were unable to take radiographs of both hips to check for LLD. Other teams have used a standard instead of a traction table to intraoperatively control lengths, with some reporting leg length reconstruction as more accurate in the traction table group (0.56 versus 1.78 mm)[ 25 ]. However, others have reported that both techniques provided equal results [ 5 ], and some have reported that leg length restoration was significantly more accurate without a traction table (2.4 versus 3.7 mm)[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the traction table, the authors were unable to take radiographs of both hips to check for LLD. Other teams have used a standard instead of a traction table to intraoperatively control lengths, with some reporting leg length reconstruction as more accurate in the traction table group (0.56 versus 1.78 mm)[ 25 ]. However, others have reported that both techniques provided equal results [ 5 ], and some have reported that leg length restoration was significantly more accurate without a traction table (2.4 versus 3.7 mm)[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different surgical approaches may affect the resistance to traction by the joint capsule. In addition, when the traction force exceeds 250 N, the vacuum negative pressure in the joint capsule will provide more than half of the antagonistic force [12, 16, 21]. The traction force in hip arthroscopic surgery obviously exceeds this threshold, so a large part of the force is to resist this vacuum negative pressure.…”
Section: Discussionmentioning
confidence: 99%